Identification and in vitro characterization of two new PCSK9 Gain of Function variants found in patients with Familial Hypercholesterolemia. Issue 1 (December 2017) - Di Taranto, Maria; Benito-Vicente, Asier; Giacobbe, Carola; Uribe, Kepa; Rubba, Paolo; Etxebarria, Aitor; Guardamagna, Ornella; Gentile, Marco; Martín, Cesar; Fortunato, Giuliana
Abstract Familial hypercholesterolemia (FH) is an autosomal dominant disease caused by pathogenic variants in genes encoding for LDL receptor (LDLR), Apolipoprotein B and Proprotein convertase subtilisin/kexin type 9 (PCSK9). Among PCSK9 variants, only Gain-of- Function (GOF) variants lead to FH. Greater attention should be paid to the classification of variants as pathogenic. Two hundred sixty nine patients with a clinical suspect of FH were screened for variants in LDLR and the patients without pathogenic variants were screened for variants in PCSK9 and APOB. Functional characterization of PCSK9 variants was performed by assessment of protein secretion, of LDLR activity in presence of PCSK9 variant proteins as well as of the LDLR affinity of the PCSK9 variants. Among 81 patients without pathogenic variants in LDLR, 7 PCSK9 heterozygotes were found, 4 of whom were carriers of variants whose role in FH pathogenesis is still unknown. Functional characterization revealed that two variants (p.(Ser636Arg) and p.(Arg357Cys)) were GOF variants. In Conclusions, we demonstrated a GOF effect of 2 PCSK9 variants that can be considered as FH-causative variants. The study highlights the important role played by functional characterization in integrating diagnostic procedures when the pathogenicity of new variants has not been previously demonstrated.